Karakteristik fisikokimia kolagen larut asam dari kulit ikan parang-parang (Chirocentrus dorab) - Mega Safithri; Kustiariyah Tarman; Pipih Suptijah; Neni Widowati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Waste of parang parang fish (Chirocentrus dorab) skin can be used as a source of collagen. Collagen isolation can be done chemically by the Acid Soluble Collagen (ASC) method. The objective of this research was to isolate collagen with ASC method and characterize their physicochemical. Collagen isolation consisted of pretreatment and hydrolysis with acids. The pretreatment used NaOH 0.1 M for 12 hours, while hydrolysis used acetic acid 0.5 M. Pretreatment results indicated that the concentration of non-collagen protein was 0.1243 mg/mL, while the yield collagen was 2.61%. The collagen had the viscosity of 6.50 cP, the denaturation temperature of 4°C, the transition temperature of 77.30°C, and the melting temperature of 153.90°C. The obtained collagen also had pH of 6.25. The fourier transform infrared (FTIR) spectra analysis showed the collagen contained amide A (3425.58), B (2924.09), I (1647.21), II (1543.05), and III (1246.02) (cm-1). The collagen also contained glycine (26.69%), proline (12.24%) and alanine (9.51%).